Kajian Abrasi dan Sedimentasi dengan Teknologi Remote Sensing di Pantai Karawang - Roberto Patar Pasaribu; Liliek Soeprijadi; Dian Sutono (Jurnal Airaha, 2019)
The existence of the coastline in the northern part of Karawang Regency is very worrying due to abrasion and sedimentation where sea water that was far from the side of the road is now on the edge of the road and several areas along the coast have been damaged affected by the abrasion. The process of abrasion and sedimentation can be monitored by using Remote Sensing technology, which is technology that uses electro magnetic waves to produce images obtained from sensors carried by satellites with the physical properties of objects observed on the surface of the earth. The purpose of this study was to determine the process of abrasion and sedimentation that occurred in the Karawang regency coast by using remote sensing technology. Based on the results of data processing and analysis conducted in 6 sub-districts along the Karawang coast, abrasion and sedimentation have occurred, where 4 villages experienced abrasion while 2 villages experienced sedimentation. The largest area formed due to abrasion occurred in Sedari village covering 166,802 hectares and the largest area formed by sedimentation occurred in Muara Cilamaya village of 276,318 hectares. The fastest speed of abrasion process occurred in Sukajaya village by 10.00 meters / year while the fastest sedimentation process was in Muara Cimalaya village at 4.50 meters / year.